ACCOUNTING STUDENTS’ KNOWLEDGE AND SKILLS: EXPECTATIONS OF EMPLOYERS - Siti Nor Adawiah Hussin; Nik Zam Nik Wan; Azilawati Abdullah @ Abd Aziz; Syuhaila Razak; Suzana San; Noraida Saidi; Siti Dalina Tumiran (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
There are widespread concerns that universities are not providing graduates with the knowledge and skills necessary to succeed in the accounting profession. Employers continue to express their discontent and demand that academics in the field of accounting take greater responsibility in addressing this issue. The aim of this article is to identify and gather new insights on the competencies and skills that employers expect accounting graduates to have obtained from university accounting education to enable them to apply those skills at the workplace. This conceptual paper will present an overview of the recent research studies on the pertinent knowledge, technical skills, and other competencies they should possess to ensure that accounting graduates are recruited in professions related to accounting. This paper will provide academics, lecturers, other scholars, and educational organisations with practical information to help produce certified accounting graduates and assists accounting students in preparing themselves with knowledge and skills that are required by employers.